2005
DOI: 10.3201/eid1105.040718
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Kala-Azar in Bangladesh

Abstract: Since 1990, South Asia has experienced a resurgence of kala-azar (visceral leishmaniasis). To determine risk factors for kala-azar, we performed cross-sectional surveys over a 3-year period in a Bangladeshi community. By history, active case detection, and serologic screening, 155 of 2,356 residents had kala-azar with onset from 2000 to 2003. Risk was highest for persons 3–45 years of age, and no significant difference by sex was seen. In age-adjusted multivariable models, 3 factors were identified: proximity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
226
4
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(264 citation statements)
references
References 14 publications
23
226
4
2
Order By: Relevance
“…4). Somewhat similar observations were found in the previous study by Bern et al (2005) who reported that more cases of VL occurred from July-September and fewer cases from January-March in Fulbaria Thana of Mymensingh district in Bangladesh.…”
Section: Monthly and Seasonal Seroprevalence Of Vlsupporting
confidence: 78%
“…4). Somewhat similar observations were found in the previous study by Bern et al (2005) who reported that more cases of VL occurred from July-September and fewer cases from January-March in Fulbaria Thana of Mymensingh district in Bangladesh.…”
Section: Monthly and Seasonal Seroprevalence Of Vlsupporting
confidence: 78%
“…We observed this pattern from 2000 to 2010 in Mymensingh District. 6,36 A similar but less marked kala-azar incidence peak was seen in 2007 in facility-based data from Bihar, India, although apparently without the PKDL echo. 37 Napier and Krisnan 22 attributed the pattern to progressively increasing population-level immunity.…”
mentioning
confidence: 86%
“…In these locations, the disease follows an endemic behavior and may, eventually, even acquire epidemiologic status (Costa: unpublished data). Several studies have pointed, in detail, to a series of risk factors associated mainly to local socioeconomic conditions, which may determine the occurrence of L. (L.) chagasi in canine and human population, like precarious housing conditions that promote the development of the vector [31][32][33][34][35] , apart from the lack of elementary sanitation and the sporadic garbage collection, which furnish the ideal microenvironments for phlebotomine reproduction 5,36 . These risk factors were observed in all regions evaluated in the present study.…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 99%